PENTINGNYA KOMUNIKASI IMAN MELALUI DISKURSUS IMAN DI DUNIA DIGITAL - Rafael Yohanes Kristianto (P3TK, Sanata Dharma University, 2016)
Fast development in science and technology provides human beings an advancement in all sectors, especially in industrial sector, health, and economics and social. The advancement also happens in information technology, resulting practicality in communicating with others without being limitted by distance and time. In this kind of situation, Church, as the part that cannot be seperated from the world, is also called to be involved in the information technology advancement and through it proclaim its mission: to proclaim Gods Kingdom to all people. The result of the research shows that communication formed in Katolistitas sets readers free from the darkness of not having enough understanding about faith into their independence: the truth in life that comes from Jesus Christ, The Way, The Truth, and The Life. This research aims to gather diversity into the unity that brings people to the true fraternity. Forms a union that is called communicatio and builds communio. This commmunio finally unites them in Katolisitas community and communio of Gods Kingdom is formed. Communication is also enhanced as the fruit of the Holy Spirit in the Church.